Analysis of Land Law Related to the Development of Tourism Sites in Traditional Land - Muhammad Fatah Bachtiar; Dimas Firmansyah Yudi Pranata; Kezia Inggreani (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The land is considered an important position in customary law because of its nature and facts. The change in land function certainly proves that there is still a conflict of interest in land tenure and other people who want to use customary village land for tourism purposes. This research is a qualitative descriptive study where the researcher uses secondary qualitative data and describes it descriptively to find answers to research questions. Based on the results and discussion, it can be found that customary land is controlled by certain customary law communities in various parts of Indonesia. The Basic Agrarian Law, also known as the UUPA, has been passed, which codifies customary land law. The provision of legal certainty over land rights is a manifestation of the role of the government and local governments in regulating human relations with the land. The National Agrarian Law came into force on September 24, 1960, after the UUPA was published and ratified as Law Number 5 of 1960 concerning Basic Agrarian Regulations (UUPA). Article 2 paragraph (3) of Law Number 5 of 1960 (UUPA) states that the right to control the state can only be exercised over autonomous regions and customary law communities if necessary and does not conflict with national interests and in accordance with government regulations.